Pelatihan Budidaya Tanaman Obat di Kelompok Tani Sumber Rejeki, Desa Peniron, Kecamatan Pejagoan, Kabupaten Kebumen - Fatmawati, Nurlaila; Rahmawati, Aulia; Rahmat Joko Nugroho, Rahmat Joko (Abdibaraya, 2024)
The community service program contained in this paper aims to educate the community about the importance of medicinal plants, their development, prospects and how to cultivate them on land owned by the community. This community service program was carried out from 31 July to 14 August 2023. This program involved 30 members of the Sumber Rejeki Farmer Group in Peniron Village, Pejagoan District, Kebumen Regency. This community service activity was assisted by the UMNU Kebumen Agrotechnology Student Organization Capacity Strengthening Program (PPK Ormawa) team. Education is carried out by conducting socialization and training on medicinal plant cultivation in farmer groups. This training activity presented information on 1) the development of medicinal plants in Indonesia, 2) prospects for medicinal plants, 3) cultivation of medicinal plants, and 4) introduction of superior varieties of medicinal plants. After the socialization session, discussions and questions and answers were held on the material presented, followed by the practice of cultivating medicinal plants. The enthusiasm of farmer group members can be seen from the many questions in the discussion session and the participation of participants in conducting training on medicinal plant cultivation. The results of the training felt by the community are 1) the land owned by the head of the farmer group has been planted with medicinal plants optimally to improve the economy of the farmer group, 2) the farmer group has new knowledge related to tillage and medicinal plant varieties, and 3) increased awareness of the village government and farmer groups of environmental sustainability by cultivating medicinal plants.